7 Nutritious rice combining high Zn content and high yield identified in preliminary yield trialin Senegal - CGIAR Research Program on Rice (2020)
In a preliminary yield trial conducted at Ndiaye, Senegal in the dry season of 2020, under direct seeding or transplanting, 12 lines including 7 high Zn lines, were identified with yields superior to best checks (Sahel 210 and Sahel 134, respectively).